2019
DOI: 10.1038/s41598-018-35833-2
|View full text |Cite
|
Sign up to set email alerts
|

Electric and Magnetic Hotspots via Hollow InSb Microspheres for Enhanced Terahertz Spectroscopy

Abstract: We study electric and magnetic hotspots in the gap between hollow InSb microspheres forming dimers and trimers. The outer radius, core volume fraction, distance, and temperature of the microspheres can be chosen to achieve field enhancement at a certain frequency corresponding to the transition between energy levels of a molecule placed in the gap. For example, utilizing 80 μ m radius spheres at a gap of 2 μ m held at a temperature of 295 K, allow electric field in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Strong local magnetic fields can be used to control or detect small quantum objects (quantum dots, atoms, and molecules) supporting magnetic optical transitions. [ 50 ] Magnetic hot‐spots are also useful for spectroscopy, [ 51 ] better enhancement of Raman scattering, fluorescence, and circular dichroism of molecules, [ 52 ] sensing, [ 53 ] and other applications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strong local magnetic fields can be used to control or detect small quantum objects (quantum dots, atoms, and molecules) supporting magnetic optical transitions. [ 50 ] Magnetic hot‐spots are also useful for spectroscopy, [ 51 ] better enhancement of Raman scattering, fluorescence, and circular dichroism of molecules, [ 52 ] sensing, [ 53 ] and other applications.…”
Section: Resultsmentioning
confidence: 99%
“…It is important for practical applications to be able to create the so-called magnetic hot spots in free space. 42 Due to structuring, the total magnetic field in the gaps can be enhanced (comparing to the Magnetic hot-spots are also useful for spectroscopy, 48 better enhancement of Raman scattering, fluorescence and circular dichroism of molecules, 49 sensing 50 and other applications.…”
Section: Resultsmentioning
confidence: 99%
“…Sadrara et al demonstrated hollow InSb microspheres forming dimers and trimers. Electric and magnetic hotspots in the gap between microspheres can be obtained, where electric field intensity enhancements of 10-2880 and magnetic field intensity enhancements of 3-61 in the frequency window 0.35-1.50 THz [52].…”
Section: Treatment Of Biomedical Samplementioning
confidence: 99%
“…presented MO measurement of several samples of InSb with different carriers and carrier concentrations for low external magnetic field and room temperatures. With these advantages, dimers and trimers of InSb particles have been studied to enhance THz spectroscopy by forming electric and magnetic hotspots in the gap between them (Bakker et al, 2015;Sadrara and Miri, 2019). Anisotropic materials like InSb in OM would make it strongly dependent on the beam combinations, allowing for countless possibilities (Roichman et al, 2008).…”
Section: Introductionmentioning
confidence: 99%